KUALITAS MAKANAN DI RESTAURANT MONA PLAZA HOTEL PEKANBARU - firmansyah, Intan; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this study was to determine the quality of food in Mona Plaza HotelPekanbaru and what efforts are being made to determine quality of food at Restaurant MonaPlaza Hotel Pekanbaru.The method used in this research is descriptive quantitative approach, which is a process ofresearch by classifying the data in the form of numbers processed by statistical methods.Essentially quantitative approach to this type of research and realize inferansial conclusion of thestudy at an error probability of rejection is nil. With quantitative research will be acquiredsignificance or significance of group differences in the relationship between the variablesstudied. In general, quantitative research with a study using a large amount. (Sasmita, 2013: 14).This study uses the concept of theoretical concepts by (Bartono PH, EM Ruffino 2005) regardingthe quality of the food this study used a Likert scale in every process of getting information frominformants.This research is getting good response from management prior to the guests about thequality of food at Restaurant Mona Plaza Hotel Pekanbaru. Therefore, the presence of the hotelresearch will further improve the quality of food at Restaurant Mona Plaza Hotel Pekanbaru.Keywords: Quality, Food, Restaurants.